Village Government Efforts to Increase Village Original Income Through Tourism Village Development in Kembang Kuning Village, Sikur District, East Lombok Regency - Muhamad Taufik Hidayat; Diswandi Diswandi (Future Tecno-Science Publisher, 2025)
This study aims to describe and analyze the efforts of the Village Government of Kembang Kuning, Sikur District, East Lombok Regency in increasing Village Original Revenue (PADes) through the development of village tourism. This research uses a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The results show that the village government has optimally utilized the potential of natural and cultural tourism by involving the community, strengthening village institutions such as the Tourism Awareness Group (Pokdarwis) and Village-Owned Enterprise (BUMDes), and developing digital promotion and homestay services. A participatory approach in planning and tourism management has been key to maintaining the sustainability of the program. However, several challenges remain, such as inadequate infrastructure, the suboptimal function of BUMDes Mart, limited tourism facilities, minimal direct involvement of the village government in the field, and the absence of a formal retribution system for local business actors. Therefore, institutional strengthening, infrastructure improvement, and more professional and inclusive tourism management are needed to ensure a sustainable increase in PADes contributions from the tourism sector.